Pelvic insufficiency fractures. Diagnostic aspects and treatment priorities - Vaitukaitis, Giedrius; Petryla, Giedrius; Šatkauskas, Igoris; Uvarovas, Valentinas (Lietuvos chirurgija, 2017)
As the average of people lives increases pelvic insufficiency fractures, their timely diagnosis and treatment are becoming more severe problem. Purpose of this article is to review the main literature databases and provide relevant, diagnostic and therapeutic principles applicable to the pelvic insufficiency fractures. This literature review includes data from articles in Pubmed and Cochrane databases. Also overview and available data are provided from Republican Vilnius University Hospital which focuses on pelvic insufficiency fracture treatment.Lithuanian hospitals do not have a common database and conducted extensive research, which could be reliable to identify exact number of pelvic insufficiency fractures.Risk factors which impact fracture deficiencies are: long-term use of corticosteroids, rheumatoid arthritis, lumbar scoliosis, fracture and prior internal fixation of the proximal femur, osteochondrosis. If patient who has a risk factor is complaining about sudden, constant pain in lower back or any other pelvic area, then pelvic insufficiency fracture needs to be considered.When pelvic insufficiency fracture is suspected the main test to be carried out is plain radiography. Monitoring plain radiography or suspecting pubic bone fracture the CT scan is recommended. Effective treatment of pelvic insufficiency fracture needs to be in conjunction with the treatment of osteoporosis and bone fracture in the pelvis.
Keywords: pelvic insufficiency fractures; osteoporosis; low energy trauma